Concise guide to information literacy - Lanning, Scott; Gerrity, Caitlin (Santa, Barbara, Carlifonia, Libraries Unlimited, 2022)
"This book is designed to help librarians lead the instruction of information literacy, a transferable and essential skill for students to navigate a tsunami of information, to sort fact from opinion and opinion from propaganda"--
Information and Information Literacy -- Information Literacy and the Library -- Curiosity, the Information Need, and the Research Question -- The Types of Information and its Sources -- Exploring the Information Landscape and Finding Resources -- Evaluating Research & Information -- Research Management and Your Role in the Research Community -- Creating a Product and Using Information -- Critically Reflecting and Sharing Your Product.
Previous edition: 2017.
Includes bibliographical references (pages 185-191) and index.
Keywords: Information literacy -- Handbooks, manuals, etc; Information retrieval -- Handbooks, manuals, etc; Research -- Methodology -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc